PERSPEKTIF KESETARAAN DAN KEADILAN GENDER HUSEIN MUHAMMAD DALAM SILANG PENDAPAT KHITAN PEREMPUAN - Hikmalisa Hikmalisa; Dona Kahfi Ma Iballa (Wahana Islamika: Jurnal Studi Keislaman, 2022)
Circumcision of women has been criticized by World Health Organization (WHO), United Nations (UN) because this practice can affect woman’s health. However, circumcision is still can be found in communities around the world, such as in Africa, the UK, and certain Asian countries including Indonesia. Furthermore, this practice is considered part of Islamic teachings by most Muslims who practice it. This thought is based on the opinion of some classical Muslim scholars such as al-Syafi’i, Hanafi, and Hambali that refer to QS. an-Nahl(16): 123 and some hadiths such as Hadith of Ummu Athiyyah. This article discusses circumcision from a feminist Kiai perspective, Husein Muhammad. This research is a qualitative descriptive study with a literature study style and uses a gender approach. The results of this study indicate that Husein Muhammad interprets the law of female circumcision by prioritizing the principles of justice and gender equality. For him, circumcision is the result of the construction by classical Muslim scholars because there is nothing in the Qur'an or Hadith that can be used as argumentation that indicates its obligation of circumcision for women. In addition, female circumcision is damaging to health means this practice is also forbidden in Islam